Monochorionic monoamniotic twin: prenatal diagnosis of cord entanglement and its management - Ismail, Hamizah; Chin, Choy Nyok; Tan, Hooi Kheng; Engku Alwi, Sharifah Huda (2017)
In year 2016, we managed three cases of monochorionic monoamniotic (MCMA) and all were found to have cord entanglements. The diagnosis was made at 17-21 weeks of gestations. The management includes: fortnightly Doppler ultrasound of the umbilical arteries and middle cerebral arteries till 28 weeks. All were routinely admitted at 29 weeks of gestation for daily cardiotocograph (CTG) with weekly biophysical profile and Doppler ultrasound. A course of dexamethasone was given between 29-32 weeks. Elective caesareans after 34 weeks were planned. Results: One case had elective caesarean at 34+5 weeks and the other two had emergency caesareans at 32+5 and 30+2 weeks for abnormal CTG. The babies are healthy with normal developmental growth. Conclusion: Prenatal diagnosis of cord entanglement is not difficult that helps triage for fetal surveillance. This is to achieve a timely optimal gestational age at delivery thus reduce the neonatal morbidity and mortality.